Situation in the Capital Market of Slovakia - Baran, Dušan (Ekonomika, 2004)
The Slovakia capital market development encompassing the beginning of 1989 when the political situation was changed till the present situation is analyzed. The main stages of privatization, namely small-scale and large-scale, and the first and second wave of the latter, are analyzed emphasizing their advantages and disadvantages. Protection of investors’ rights is one of the main issues of the present capital market in Slovakia. The possible ways of dealing with this problem and consequences are discussed also. Statistical data showing the development of the Slovak capital market in the context of European countries are presented.